Strategi Percepatan Penghapusan Kemiskinan Ekstrem di Provinsi Sulawesi Tengah: Pendekatan Konvergensi dan Inovasi Program - Dian Astuti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Extreme poverty in Central Sulawesi remains a significant challenge that demands an integrated strategy. This study evaluates the effectiveness of government programs, including Gercep Gaskan Berdaya and PADUNGKU, in accelerating the eradication of extreme poverty. Secondary data from the 2023 P3KE Update and the 2024 BPS were analyzed using multiple linear regression. The findings reveal a 0.64% reduction in extreme poverty during the 2023-2024 period, with notable declines in Donggala (0.95%) and Poso (0.93%). The "Gercep Gaskan Berdaya" program, which combines cash assistance and entrepreneurial training, successfully increased the income of impoverished households; however, aid distribution often faced challenges in areas with limited access. Despite these efforts, Parigi Moutong and Poso districts still have the highest numbers of people living in extreme poverty, indicating a need for program intensification. While existing programs have shown positive outcomes, long-term success heavily depends on improving infrastructure access, enhancing cross-sectoral coordination, and providing better basic services. The convergence and innovation of socio-economic programs, along with improved infrastructure access, have proven effective, although challenges persist in remote areas. A comprehensive approach and enhanced coordination are required to meet the target of eradicating extreme poverty by 2024.